Potensi Coriatin dan Coriamyrtin Helixanthera sessiliflora (Merr.) Denser sebagai Kandidat Obat Penurun Hipertensi; Kajian in silico - Sari, Dewi Ratih Tirto; Pratiwi, Maulidia Riska; Yusuf, Heny; Azkiyah, Siti Zamilatul (BIOMARAS : Journal of Life Science and Technology, 2024)
This study investigated bioactive compounds from Loranthaceae as antihypertension drug candidates through in silico approach. Coriatin and coriamyrtin structure as a targeted ligand was carried out from PubChem NCBI, lisinopril as a native ligand for control was used in this study. Targeted protein that chose for hypertension was angiotensin converting enzyme (ACE), which retrieved from protein data bank. Ligands and protein were docked by Molegro virtual docker version 5.0 and analyzed by PyMol 2.3 and Discovery studio version 21.1.1. docking results showed that coriatin and coriamyrtin posed interaction at the same sites of ACE protein as well as lisinopril. Some active residues of lisinopril that identified on coriatin were GLN281, HIS383, and TYR520, while residues of coriamyrtin that were same as lisinopril were GLU384, GLU411, HIS513, and HIS387. The same binding sites of coriatin and coriamyrtin with lisinopril indicated that both of compounds have potential activity as well as lisinopril. In conclusion, coriatin and coriamyrtin were potentially as antihypertension drug candidates. Further in vivo and in vitro should be conducted for future investigation.